Point-of-care glucose testing: On-site competency assessment - Jaray Tongtoyai (2018)
© Emerald Group Publishing Limited. Purpose – The purpose of this pilot paper is to use on-site assessment to determine common non-compliance in point-of-care (POC) glucose testing, deficiencies that should be improved by the POC team or emphasized in further training. Design/methodology/approach – Assessment forms for POC site and staff competency were developed and used for direct observation in four POC sites. Nurses were sampled in these sites. Findings – The on-site assessment demonstrated that initial operator training was insufficient. Only three of 15 nurses achieved a satisfactory score on the first assessment. In all nine participants who had been assessed at least twice improved their performance. In total, 16 (30 percent) of 53 competency items were not achieved, so these should be addressed during refresher training. Improved compliance with the checklist was observed in two of four POC sites. Research limitations/implications – Medical students and residents also perform the test, so more representative samples are needed. Practical implications – The assessment of staff performance in the workplace with constructive input and POC site inspections to identify common deficiencies are recommended. Refresher trainings should be focussed on the deficiencies identified. Social implications – Assessing staff performance in the workplace with constructive input and POC site inspections to identify common deficiencies are recommended. Refresher trainings should focus on deficiencies. Originality/value – This study involved directly observing POC site staff during glucose testing. The assessment forms were based on ISO 22870:2006 technical requirements.